Catch composition of a set bag net (SBN) used for Acetes trapping in the estuarine waters of Kedah, Peninsular Malaysia. - Amani, A.A.; Arshad , Aziz; Amin, Nurul; Abd Aziz, Nor Azwady (Academic Journals, 2011)
A study was conducted for a 12-month period, from June 2008 to May 2009 based on the catch data to determine the catch composition of Set Bag Net (SBN) that is a type of fishing net laid down to catch Acetes shrimps that move along the estuary of Merbok River in the state of Kedah, Peninsular Malaysia. Bag net is a static traditional gear with a cod end mesh size measuring 0.5 cm. The results showed that total catches of the bag net over a year period were constituted of three major catch groups viz. Acetes shrimps (89%), juvenile fishes (9%) and other non-Acetes shrimps (2%). The annual mean percentage composition of sergestid shrimps comprised of A. japonicus, A. vulgaris and A. indicus were found to be 89, 7 and 4%, respectively. The gear is very selective and besides Acetes there was also a small proportion of fish juvenile being caught. Seven species of juvenile fishes were recorded throughout the catch period however; their mean total abundance was very low (9%). Penaeid shrimp was the only group of non-Acetes shrimp been recorded. Based on the analyzed catch composition data, it could be concluded that SBN is Acetes-selective and not causing significant great damage to the juvenile fish population inhabiting the study area.